ARTICLE ABOUT THE NEGATIVE IMPACT OF ENVIRONMENTAL POLLUTION ON THE ECONOMIC INSTITUTION (PROSPECTS FOR THE YEAR 2035) - Hanane, Slaouti; Trifa, Mohamed (The journal of contemporary issues in business and government, 2024)
Regardless of their nature of operations, Economic institutions, strive for economic growth with the aim of maximizing their profits. However, in the process of conducting their activities, various negative effects on the environment occur, such as pollution and resource depletion. In order to integrate the environmental and social dimensions into the economic institution's strategy, governments have taken a series of measures and actions that align with the institution's activities and the achievement of sustainable development based on three fundamental principles: economic growth, social justice, and environmental protection. The external environmental assessment of the institution contributes to the effectiveness of its management, indicating the extent to which the institution is achieving its objectives by aligning its resources. This assessment allows for the identification of opportunities to exploit and threats or risks that can be faced or mitigated.